2004
DOI: 10.1007/s00244-003-2266-8
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccumulation Profiles of Chemical Contaminants in Fish from the Lower Willamette River, Portland Harbor, Oregon

Abstract: Twenty-five PCBs (polychlorinated biphenyls), 15 organochlorine (OC) pesticides, and mercury were determined in fish from the Willamette River in Oregon, including a Portland Harbor superfund site. Fish were collected during the summer of 2000 along a 20-mile stretch of the lower Willamette River. Concentrations of sumPCBs (sum of 25 individually determined PCB congeners) and sumDDTs (sum of p,p'-DDT, p,p'-DDE, and p,p'-DDD) in fish ranged from 14 to 530 and from 18 to 510 ng/g-wet weight, respectively. SumPCB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 12 publications
4
24
0
Order By: Relevance
“…Largemouth bass living in these areas presented levels of dieldrin in fat of 0.5 ppm and concentrations of DDT of 13 ppm, while the DDT concentration in the sediments was much lower than those for p,p′-DDE (0.06-0.6 ppm) (Marburger et al, 2002). Other studies have reported p,p′-DDE concentrations of 1.5 ppm in fish from the Adriatic Sea (Storelli et al, 2004) and 0.5 ppm in fish from Portland Harbor (Sethajintanin et al, 2004) indicating that the concentrations obtained in this study are environmentally relevant. We focused on p,p′-DDE and dieldrin because these are relatively stable metabolites of the parent compounds p,p′-DDT and aldrin.…”
Section: Discussionmentioning
confidence: 80%
“…Largemouth bass living in these areas presented levels of dieldrin in fat of 0.5 ppm and concentrations of DDT of 13 ppm, while the DDT concentration in the sediments was much lower than those for p,p′-DDE (0.06-0.6 ppm) (Marburger et al, 2002). Other studies have reported p,p′-DDE concentrations of 1.5 ppm in fish from the Adriatic Sea (Storelli et al, 2004) and 0.5 ppm in fish from Portland Harbor (Sethajintanin et al, 2004) indicating that the concentrations obtained in this study are environmentally relevant. We focused on p,p′-DDE and dieldrin because these are relatively stable metabolites of the parent compounds p,p′-DDT and aldrin.…”
Section: Discussionmentioning
confidence: 80%
“…Dominance of pp-DDE, among the DDT metabolites reflects earlier usage of DDT in the catchments. Sethajintanin et al (2004) and Yang et al (2007) have also reported dominance of pp-DDE in the fish samples. pp-DDE is a highly persistent metabolite in the environment and organisms.…”
Section: Resultsmentioning
confidence: 99%
“…The increase in the PBDE load of smallmouth bass indicates the importance of the benthic-pelagic link created by the invasion of non-native species. Smallmouth bass has previously been observed to accumulate higher levels of persistent organohalogen compounds and mercury than other organisms due to trophic position (Kwon et al, 2006;Sethajintanin et al, 2004), but only recently has the importance of the direct link between benthic uptake and predatory fish been observed (Carlson et al, 2010;Hogan et al, 2007). Prior to the invasion of the round goby, the lack of a benthic link allowed for the sequestration of such persistent compounds to benthic organisms (Moermond et al, 2004).…”
Section: Symbolmentioning
confidence: 96%